A perspectiva do valor e o valor das perspectivas - Silva Neto, João Pereira da (2020)
The aim of this thesis is to investigate Nietzsche’s conceptions about truth and knowledge, taking the problem of values and the relation between perspective and life in Nietzsche’s thinking as research axes. This research, starting from the Nietzschean texts of youth, reaches its last posthumous writings, accompanying the interweaving of the Nietzschean conclusions about the traditional conception of truth and nihilism. In this reading, knowledge appears as a form of human activity that undergoes a reappraisal, based on the Nietzschean conclusions about the need to overcome nihilism. For Nietzsche, the conception of traditional knowledge would be based on values that are produced from the need of conservation of the human species, that are understood by the philosopher as inefficient to overcome the value devaluation process. Thus, unless science and philosophy were freed from the bonds of a conception of truth and knowledge that would culminate in the immobilization of the will, every philosophical and scientific procedure would be doomed to an unavoidable corruption of its foundations and value. Perspectivism is understood here as the fundamental characteristic of a way of making philosophy which, moving away from the dogmatism of traditional philosophy and science, approaches itself of an art form. In this way, the Nietzschean perspectivism would have in the creation of values its fundamental object. Thus, based on the presupposition of a future philosophy of values, which has its foundations in the understanding of perspective as an attitude committed to life-strengthening values, the philosopher seeks to opposite itself to the hegemony of the traditional conception of knowledge, which has its foundations in values of decadence.